Mediamorfosis Industri Media Televisi: Studi Lembaga Bisnis EMTEK pada Platform Digital vidio.com - Achmad Budiman Sudarsono; Helen Olivia (COMMENTATE: Journal of Communication Management, 2021)
Changes in communication technology are currently changing the behavior of society in general, this is indicated by the use of mobile media, which has been used as a communication medium, is now used as a medium for watching television programs. This mediamorphosis phenomenon is used by MNC Group and Emtek Group to transform conventional media into digital media. This change encourages media owners to make digital changes in the broadcasting sector in Indonesia. The MNC group has digital television broadcasting under the name MeTube, while the Emtek group has the name Vidio.com. Not many televisions in Indonesia have changed conventional media broadcasting to digital media, benefiting the MNC group and the Emtek group. The perspective of this study is referred to as a channel for the process of exchanging commodities in the free market in order to compete and provide benefits and satisfaction to the public. As for this study using a qualitative method with a constructivist paradigm, while the aim of the researcher is to try to explore the problem of changes made by the media industry from conventional to online streaming broadcasts that change people to watch television shows anywhere. While the results of this study are changes in technological developments, especially communication and information technology, giving impetus to the media to change their business strategies. With the development of convergence technology, media are required to adapt by distributing content through many platforms at the same time as the current media industry terminology changes.